Socio-demographic variation on tourism expenditure in Melaka UNESCO world heritage area - Ab Rahman, Syakir Amir; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (American Scientific Publishers, 2017)
Melaka City has been designated as UNESCO World Heritage site since 2008 that offers authentic heritage and cultural attractions to tourists worldwide. The study explores the domestic and inbound tourists spending pattern and its socio-demographic effects to the expenditure pattern in the Melaka Heritage area. 1000 diary record surveys were collected from domestic and inbound tourists and the analysis of variance (ANOVA) was used to test the research hypothesis. Socio-demographic characteristics including age, marital status, occupation, education level, first-time and repeat visit were found to significantly affect domestic tourism expenditure while only age, marital status and purpose of visit were found to significantly affect inbound tourism expenditure. © 2017 American Scientific Publishers. All rights reserved